Future career planning - Panggabean, Krislegawana (Trigin Institute, 2023)
Career planning is a process that starts from knowing and understanding oneself, realizing the opportunities within himself and various choices with all his abilities, classifying choices, making decisions, developing his future career in achieving goals and plans to make plans for a job. The three main aspects of career planning are knowledge and understanding of oneself, knowledge and understanding of work, and the right way of thinking between oneself and the world of work. which is the main key in planning a future career that is in accordance with its capabilities will also be able to know the interests, talents, strengths and weaknesses that we have. So that it can facilitate us in planning our future careers